Analysis of Students’ Politeness in Indonesian in Interacting With Grade IV Teachers at SDN 1 Karangdempel - Sri Sobiyah; Farhan Saefudin Wahid; Didik Tri Setiyoko (International Journal of Education and Literature, 2025)
One of the factors that determine the success of a character-based language learning process is the interaction between teachers and students. Polite language from students can show that they have the expected character, in addition to showing that teachers have helped students behave with polite language. Classes often do not meet expectations. Many students are still unable to pronounce good words. In the last two decades, there has been a significant decline in the implementation of polite language originating from Brebes Regency. Children believe that using impolite language is acceptable to their friends and following trends in their environment because of the abundance of impolite language in society. This causes people to use Indonesian less. The purpose of this study is to determine the politeness of Indonesian language students in interacting with teachers in grade IV SDN 1 Karangdempel. This study uses a qualitative research type. The approach used in this study is qualitative research with a descriptive approach. The location of this research is SDN 1 Karangdempel, Losari District, Brebes Regency, Central Java, Indonesia 52212. Based on research that has been done on the analysis of the form of politeness in Indonesian language in interacting with teachers in the learning process is polite. Because, in the implementation of the learning process can include several maxims including: Maxim of wisdom/wisdom, maxim of generosity, maxim of praise/appreciation, maxim of humility/simplicity, maxim of agreement/agreement, and maxim of sympathy. From several existing maxims it can be concluded that the maxim of humility/simplicity is the one most frequently found in the data of politeness in Indonesian language in class IV SDN 1 Karangdempel, Brebes Regency, because that maxim is the one that occurs most often in learning activities.